Pathways to low-carbon agriculture: soil management, carbon storage, and wheat productivity in Paraná, Brazil - Santi, Anderson; Giongo, Vanderlise; Amaral, André Júlio do; Salviano, Alessandra Monteiro; Santana, Mônica da Silva; Battistelli, Tatiane; Silva, Bruno Ricardo; Pires, Bruno Stefano (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to evaluate 12 wheat farms in the state of Paraná, Brazil, in order to identify structural and functional soil property patterns that explain wheat productivity and soil carbon stocks, aiming to support improvements in soil management and guide the transition to low-carbon agriculture. Soil samples were collected at the depths of 0–10, 10–20, and 20–30 cm on farms under no-tillage systems, of which 90% adopt crop rotation. On the studied farms, enhancing crop rotation is necessary to increase soil carbon sequestration, resulting in a greater resilience to extreme climate events. The factor analysis shows that fertility, acidity, and physical properties shape soil patterns across the 12 farms. The low predictive power of the regression models for productivity suggests that unmeasured factors, such as climate and phytosanitary conditions, influence yield, highlighting the need of integrated soil fertility management to support productivity and carbon sequestration. The subindices soil and water conservation, soil fertility chemistry, and soil structural quality exhibit the lowest performances and, therefore, require prioritization in improvement programs for wheat production systems in the studied region.
Keywords: farming systems; no-tillage; soil fertility; sustainable agriculture; wheat yield